Bright Lesion Detection in Color Fundus Images Based on Texture Features - Ratna Bhargavi V; Ranjan K. Senapati (Institute of Advanced Engineering and Science, 2016)
In this paper a computer aided screening system for the detection of bright lesions or exudates using color fundus images is proposed. The proposed screening system is used to identify the suspicious regions for bright lesions. A texture feature extraction method is also demonstrated to describe the characteristics of region of interest. In final stage the normal and abnormal images are classified using Support vector machine classifier. Our proposed system obtained the effective detection performance compared to some of the state–of–art methods.